Measurement and Misrepresentation - Chambers, R. J. (Management Science, 1960)
The possibility of measuring does not necessarily lead to the presentation of relevant information for decision-making in business. This is demonstrated by reference to accounting methods and to profit computation in particular. Accounting processes have become formalized to the point where they misrepresent financial results and position; the probability that resources will be used efficiently and that equity between parties of interest will be served is materially reduced by lack of care in the definition of significant concepts and the concurrent acceptance of procedures which have directly opposite justifications and consequences. As the speed of information processing increases and computational refinements develop, a corresponding effort is necessary to redefine in operationally relevant terms, or to sharpen the definition of, such key concepts as profit, capital, cost. The history of the development of accounting and auxiliary calculations illustrates the consequences of permitting a measuring and communicating system to become institutionalized. Some suggestions for improving the relevance of accounting and similar information are made.